Preliminary study on spallation target characteristics in an Accelerator-Driven system. (September 2021) - Lin, Chia-Nien; Wu, Shin-Rong; Wu, Shang-Chien; Chao, Der-Sheng; Liang, Jenq-Horng
Abstract: This study aims to investigate the neutronic characteristics of spallation targets for Accelerator-Driven subcritical System (ADS) and find the optimal target design for reducing the strength of the required beam current. All the calculations were conducted using the MCNP6.1 with cross-section library ENDF/B-VII. In this study, the influence of several parameters on spallation targets is investigated, such as neutron production with various spallation target layouts, spallation neutron distribution with different proton beam energy levels, and spallation neutron spectrum. Highlights: Neutron production analysis with different spallation target geometries. Spatial and energy neutron flux distribution for spallation target. Fixed-source problem simulation with high proton beam fixed-source.